ANALISIS SISTREM AGRIBISNIS INDUSTRI RUMAH TANGGA TAHU DAN TEMPE (Studi Kasus di Kabupaten Nganjuk) - Sumanto Sumanto; Masyhuri Masyhuri; Sutrilah Sutrilah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2000)
Protein is need keep increasing in arow increasion of population and income amount, while in other hand supply of protein source in Indonesia isn't enough yet. This need substitution protein source that easy to get and cheap. From WS contain, soybean with derivative product tahu and tempe is high protein source, non colesterol, contain of essential amino acid for body, easy to get and not so exspensive, where in economic crisis its demand were increasing because of instable price from other protein source; chiken, cow, goat, meat, etc.In economic crisis condition tahu and tempe producer also face with soybean jump price, for example in luny 1998 soybean price Rp. 2.300,- / kg no more two months after move up Rp. 4.400,- / kg even rare in market, that condition could make direct effect in production and product price determine (consumer service)Related with confinuoing tahu and tempe product examined agribusiness all system that limited use : (a) each 30 samples to soybean demand in home industry, (b) effeciency reachment efforts and production process each 30 samples and (c) each 100 samples at output demand in consument point.Used data in analysis is primer data where three of data types taken proposively in Nganjuk regency area. Used analysis instrument is Shazam with Ordinary Least Square (OLS) methode, for confinuoing of analysis result well discussed to solve the phenomenon that three of agribusiness sub sector exist.The soybean demand as the tahu raw material was inelastic (- 0.71802). Capital showed the most significant influence (0.71236), so did the plant's capacity (0.731060). The kedelai demand as the tempe raw material was inelastic (-0.85791). The tempe producer's capital was the most significant effect (0.51957) and the tempe processing plant's capacity had significant effect (0.64195).From the tahu production it was obtained TER of 0:99999542549667, in which the soybean and the fuel had been allocated efficiently, water addition was needed where as the workers had to be reduced. From the tempe production it was obtained TER of 0.9993365823 and the human labor was allocated efficiently; additional soybean, fuel and machine labor were still required.The tahu demand was inelastic (- 0.80468), and it was a normal good, wheat flour (-0.536080) was complementary good, whereas chicken (0.431800), lamb (0.789220), beef (0.615360) and fish (0.445760) were substituting goods. The tempe demand was elastic (-1.5042), the average consumption was 0.86 kg tempe per 100 consumers, with the price of Rp 3,267.- per kg. The chicken has the most significant effect (1.1847).